2001
DOI: 10.1097/00005768-200106000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual responses in the heat after brief intravenous versus oral rehydration

Abstract: It was concluded that ORAL resulted in lower RPE, thirst, and TS compared with CON and IV during exercise in the heat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 16 publications
2
30
1
1
Order By: Relevance
“…The effort was perceived to be greater, indicating that the psychological response paralleled the exaggerated physiologic responses. 8,[35][36][37][38] Put simply, dehydrated runners had to work harder (and knew it) to accomplish a task that was easier when they were less dehydrated.…”
Section: Submaximal Running (Hys and Dys)mentioning
confidence: 99%
See 1 more Smart Citation
“…The effort was perceived to be greater, indicating that the psychological response paralleled the exaggerated physiologic responses. 8,[35][36][37][38] Put simply, dehydrated runners had to work harder (and knew it) to accomplish a task that was easier when they were less dehydrated.…”
Section: Submaximal Running (Hys and Dys)mentioning
confidence: 99%
“…5 Evidence for greater physiologic strain and resultant compromised performance includes increased HR, decreased stroke volume, thermoregulatory strain (or the physiologic response to excessive heat production and storage in the absence of heat dissipation), stress response, perception of effort and anticipatory regulation of pace, hypovolemia, hyperosmolality, and a decrease in percentage of total work completed, among other factors. 1,[6][7][8][9][10][11][12] Because exercise intensity is the single greatest influence on the rate of core temperature rise in the heat, [13][14][15] authors of many of these laboratory studies control intensity. Also regulated in well-controlled studies are other variables that could compromise consistency among trials, including ambient temperature, humidity, length of exercise, time of day, nutritional intake, clothing, airflow, and heat acclimatization status.…”
mentioning
confidence: 99%
“…4 Oral REHY provides oropharyngeal stimulation, important for perceptual and some physiologic responses. [28][29][30] Bypassing this reflex with IV REHY, however, eliminates the potential disadvantage of delayed gastric emptying or intestinal fluid absorption or discomfort. [31][32][33] Direct comparisons are obviously contingent upon OR fluid tolerance, which can be impaired during significant dehydration.…”
Section: Discussionmentioning
confidence: 99%
“…13 Perceived thirst did not differ among treatment drinks at any point during the 60-minute rehydration period. Scientists 26,27 have observed that the act of drinking, not a decrease in OSM p or [Na þ ] p , is responsible for the rapid satiety of thirst. Additionally, the Na þ content of the fluid consumed appears to have a minimal effect on thirst.…”
Section: Perceptual Indicatorsmentioning
confidence: 99%